2009
DOI: 10.1111/j.1468-2389.2009.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive Work Behavior Among White‐Collar Employees: A study from Turkey

Abstract: The current study was designed to evaluate the magnitude and types of counterproductive work behaviors (CWBs) among a group of white-collar employees from different firms. A total of 766 employees voluntarily participated in our study. We focused especially on employees' perceptions of their work environment and on their affective responses to those perceptions. Data were dependent on self-reporting and privacy, and anonymity measures were taken into account. The five different instruments used to evaluate job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
1
19
2
2
Order By: Relevance
“…This diverges from previous findings that have found a significant relationship between the two variables (e.g. Chen & Spector, 1992;Bayram, Gursakal, & Bilgel, 2009), but is not as surprising as the result for organizational justice. The lack of a significant result may be due to the fact that this study investigated overall CWB, rather than separating CWB into separate dimensions.…”
Section: Main Effectscontrasting
confidence: 99%
“…This diverges from previous findings that have found a significant relationship between the two variables (e.g. Chen & Spector, 1992;Bayram, Gursakal, & Bilgel, 2009), but is not as surprising as the result for organizational justice. The lack of a significant result may be due to the fact that this study investigated overall CWB, rather than separating CWB into separate dimensions.…”
Section: Main Effectscontrasting
confidence: 99%
“…Our results also indicated that the percentages of CWB among Chinese knowledge workers were relatively high. Compared with CWB among white‐collar workers in Turkey (Bayram, Gursakal, & Bilgel, ), the frequencies of CWB among knowledge workers in China were higher. The mean frequency of production deviance was 13.5% in Bayram et al.…”
Section: Discussionmentioning
confidence: 88%
“…Our results also indicated that the percentages of CWB among Chinese knowledge workers were relatively high. Compared with CWB among white-collar workers in Turkey (Bayram, Gursakal, & Bilgel, 2009), the frequencies of CWB among knowledge workers in China were higher.The mean frequency of production deviance was 13.5% in Bayram et al's study, while in our study the mean frequency of loophole seeking, which was similar to production deviance, was 44.0%. Our study provides strong empirical evidence for the argument that CWBs among knowledge workers in China are very prevalent.Thus, Chinese managers should pay attention to the most frequently reported CWB.…”
Section: Frequencies Of Cwbmentioning
confidence: 86%
“…Noting the positive role of OCB within educational institutions (Belogolovsky & Somech, 2010;Oplatka, 2009), however, with the pressure involved within the academic career (Fox & Stallworth, 2010), CWB would seem to be a type of normal response for teachers under such circumstances (Fox, Spector, & Miles, 2001). In essence, teachers are also normal individuals, hence exhibits similar behaviors as of the typical employees (Bayram, Gursakal, & Bilgel, 2009). Nevertheless, CWB is still considered quite harmful to both the people working within and to the organization itself (Gruys & Sackett, 2003;Robinson & Bennett, 1995;Sackett, 2002).…”
Section: Introductionmentioning
confidence: 99%